The pancreas. Issue 11 (November 2020) - McGuckin, Ellen; Cade, Jennifer E.; Hanison, James
Abstract: The pancreas plays a vital role in coordinating and regulating digestion and nutrient metabolism and is a mixed endocrine and exocrine organ. The endocrine organ secretes a number of hormones with diverse effects including glycaemic control, gut motility, gut secretions and appetite. Exocrine function is explored and the role that some enzymes play as biomarkers for pancreatitis. This article explores the complex homeostatic control of the synthetic and secretory functions of the pancreas and reviews the physiology of the secreted hormones and enzymes.